One‐year conditional survival of dogs and cats with invasive mammary carcinomas: A concept inspired from human breast cancer. (28th September 2020) - Chocteau, Florian; Mordelet, Valentin; Dagher, Elie; Loussouarn, Delphine; Abadie, Jérôme; Nguyen, Frédérique
Abstract: Numerous studies have described the prognostic factors of canine and feline mammary carcinomas (MCs), that is, variables that predict patient survival after diagnosis. But how does survival estimation evolve in patients that escaped early death from their cancer? In human oncology, conditional survival (CS), the probability of surviving X further years when cancer patients have already survived Y years, is used to analyse cancer outcomes in a long‐term perspective. In this cohort of 344 dogs and 342 cats with surgically removed stage I to III invasive MCs, with a minimal follow‐up of 2 years, we calculated the 1‐year CS, that is, the probability for patients that have survived 1 year, to survive or to die from cancer during the subsequent year. The 1‐year conditional specific survival probabilities were 59% and 48% at diagnosis of invasive MC respectively in dogs and cats, and 80% and 52% in 1‐year surviving dogs and cats respectively, suggesting that 1‐year surviving dogs were relatively protected from cancer‐related death, whereas feline MCs remained life‐threatening cancers for longer periods of time. Among the most significant parameters associated with CS in surviving dogs and cats were the nodal stage and lymphovascular invasion, as well as patient age, cancer stage and margin status in surviving dogs. By comparison, tumour size and the histological grade did not significantly alter CS probabilities in surviving dogs and cats. Conditional survival may be considered a very interesting tool for veterinary practitioners to estimate the likely outcome of cancer survivors.